Emotional self-regulation and reading comprehension in the digital age - CEBALLOS-MARÓN, Natalia Andrea (2020)
It is of great importance to understand the necessity to promote emotional regulation in children in order to improve their reading comprehension. In the current health crisis, which is studied in relation to Argentina, emotional bonds and learning must be developed using the available digital tools. In this article, we will address the importance of self-regulation in school-age children and reading comprehension, from the perspective of educational technologies. The objective is to demonstrate how to achieve an effective connection between emotional and cognitive processes in the educational environment. Data are presented on an investigation carried out in the province of Córdoba, Argentina, and on two tools that emerged from it: digitized TIRC task to measure cognitive reevaluation; and Narrative Action Reading Comprehension rubric (CLAN), which studies this competence by linguistic levels. Finally, some recommendations are described to take into account from the educators' perspective.Keywords: self-regulation, reading comprehension, digital age, education.